Structural and Functional Effects of C5aR1 Antagonism in a Rat Model of Neonatal Hypoxic-Ischemic Encephalopathy - Saadat, Angela; Pallera, Haree; Lattanzio, Frank; Owens, Daley; Gaines, Amy; Ravi, Sai Susmitha; Shah, Tushar (Developmental neuroscience, 2025)
Abstract Introduction: The complement response activates upon reperfusion in neonatal hypoxic-ischemic encephalopathy (HIE) and contributes to excessive neuroinflammation and worse outcomes. C5a is a powerful anaphylatoxin central to each of the complement pathways, and its engagement with C5aR1 is directly tied to brain injury and neuronal death. Reasoning C5aR1 antagonism can decrease excessive neuroinflammation and thereby improve neurological and functional outcomes, we tested this hypothesis in a rat model of HIE with PMX205, a small molecule that inhibits C5a-C5aR1 interaction. Methods: Term-equivalent pups (P10-12) were subjected to mild-moderate HIE by Vannucci’s method and treated with PMX205. We compared motor and cognitive outcomes with two behavioral tests each (food handling and accelerod; novel object recognition [NOR] and open field) to improve the accuracy of our conclusions. Results: Improvements were observed in fine motor function, balance, and exploratory behaviors, but little to no improvement in recognition memory and gross motor function. Lesion area and histological assessments showed robust cortical neuroprotection from treatment but persistent injury to the CA1 region of the hippocampus. Better structural and functional outcomes were seen within 1 day of treatment, suggesting C5aR1 antagonism beyond the latent injury phase may impair recovery. In a dose-response experiment, cerebral area loss from injury was improved only in female rats, suggesting underlying sexual dimorphisms in the complement response. Conclusion: These results demonstrate proof-of-concept for targeting C5aR1 signaling in neonatal HIE with PMX205 and underscore the role of sex in hypoxic-ischemic injury. Introduction: The complement response activates upon reperfusion in neonatal hypoxic-ischemic encephalopathy (HIE) and contributes to excessive neuroinflammation and worse outcomes. C5a is a powerful anaphylatoxin central to each of the complement pathways, and its engagement with C5aR1 is directly tied to brain injury and neuronal death. Reasoning C5aR1 antagonism can decrease excessive neuroinflammation and thereby improve neurological and functional outcomes, we tested this hypothesis in a rat model of HIE with PMX205, a small molecule that inhibits C5a-C5aR1 interaction. Methods: Term-equivalent pups (P10-12) were subjected to mild-moderate HIE by Vannucci’s method and treated with PMX205. We compared motor and cognitive outcomes with two behavioral tests each (food handling and accelerod; novel object recognition [NOR] and open field) to improve the accuracy of our conclusions. Results: Improvements were observed in fine motor function, balance, and exploratory behaviors, but little to no improvement in recognition memory and gross motor function. Lesion area and histological assessments showed robust cortical neuroprotection from treatment but persistent injury to the CA1 region of the hippocampus. Better structural and functional outcomes were seen within 1 day of treatment, suggesting C5aR1 antagonism beyond the latent injury phase may impair recovery. In a dose-response experiment, cerebral area loss from injury was improved only in female rats, suggesting underlying sexual dimorphisms in the complement response. Conclusion: These results demonstrate proof-of-concept for targeting C5aR1 signaling in neonatal HIE with PMX205 and underscore the role of sex in hypoxic-ischemic injury. Plain Language SummaryIn this study, we tested a new treatment for a disease in babies called hypoxic-ischemic encephalopathy (HIE). HIE is caused by restricted oxygen and blood flow around the time of birth, and most damage is caused when blood flow is restored. One reason for this is excess inflammation, which happens because a large amount of specific proteins and chemicals are released. Some inflammation is protective, but excessive inflammation injures healthy tissue, and in HIE this contributes to lifelong physical and mental disabilities, even death. The only treatment for HIE is cooling therapy, but even with this treatment many infants still do not survive or live with permanent disability. We mimicked the disease in rats and then gave them a drug that prevents excess inflammation by binding and disabling specific proteins. We measured improvement by comparing physical and mental abilities and brain damage in the treated rats to untreated and normal rats. Overall, the drug improved many but not all skills and parts of the brain harmed by the disease. More testing needs to be done to determine the optimal dose and if there is additional benefit when the drug is combined with cooling therapy. In closing, our results show this treatment warrants further development and could help infants grow up with less hardship and lead better, healthier lives.